ANALISA PENINGKATAN GAIN ANTENNA MENGGUNAKAN ARRAY FEEDING PADA FREKUENSI X BAND - Bambang Bagus; Sukahir; Ayub Wimatra; Fatmawati Sabur (Jurnal Penelitian)
Microstrip antennas are antennas that are often applied because of their simple structure and easy to apply. The purpose of the experiment was to design and analyze the results of microstrip antennas in CST applications with a frequency of 10.5 GHz. Experiments used single patch antennas, 1 x 2 arrays using 2 patches and 1 x 4 antenna arrays using 4 antenna patches. Each series has different characteristics of return loss, gain, VSWR, and axial ratio. Based on these experiments, the results were obtained, namely the return loss of single patch, array 1x2 and array 1 x 4 respectively were -19 dB, -11 dB and -19 dB, while antenna gain was 2.9 times, 9.09 times and 2.27 times. The lowest VSWR value is found in the single patch circuit while the highest is found in the 1 x 4 array antenna. The axial ratio of a single patch and an array of 1 x 4 has the same value of 40, while a series of arrays of 1 x 2 has an axial ratio value of 35. Based on these results, it can be concluded that each circuit has a specification of values that are not the same, but it is still included in the appropriate antenna criteria, namely VSWR <2 and return loss below -10 dB.